Genetic variation for tolerance to pre-harvest sprouting in mungbean (Vigna radiata) genotypes - Gupta,Soma; Aski,Muraleedhar; Mishra,Gyan Prakash; Yadav,Prachi S.; Tripathi,Kuldeep; Lal,Sandeep Kumar; Jain,Simran; Nair,Ramakrishnan Madhavan; Dikshit,Harsh Kumar (PeerJ, 2024)
Pre-harvest sprouting (PHS) is one of the important abiotic stresses in mungbean which significantly reduces yield and quality of the produce. This study was conducted to evaluate the genetic variability for tolerance to pre-harvest sprouting in diverse mungbean genotypes while simultaneously deciphering the association of yield contributing traits with PHS. Eighty-three diverse mungbean genotypes (23 released varieties, 23 advanced breeding lines and 37 exotic germplasm lines) were investigated for tolerance to PHS, water imbibition capacities by pods, pod and seed physical traits. Wide variation in PHS was recorded which ranged between 17.8% to 81% (mean value 54.34%). Germplasm lines exhibited higher tolerance to PHS than the high-yielding released varieties. Correlation analysis revealed PHS to be positively associated with water imbibition capacity by pods (r = 0.21) and germinated pod % (r = 0.78). Pod length (r = −0.13) and seeds per pod (r = −0.13) were negatively influencing PHS. Positive associations between PHS and water imbibition capacity by pods, germinated pod % and 100-seed weight was further confirmed by multivariate analysis. Small-seeded genotypes having 100-seed weight <3 g exhibited higher tolerance to PHS compared to bold-seeded genotypes having 100-seed weight more than 3.5 g. Fresh seed germination among the selected PHS tolerant and susceptible genotypes ranged from 42% (M 204) to 98% (Pusa 1131). A positive association (r = 0.79) was recorded between fresh seed germination and PHS. Genotypes M 1255, M 145, M 422, M 1421 identified as potential genetic donors against PHS could be utilized in mungbean breeding programs.
Keywords: Mungbean; Pre-harvest sprouting; Genetic variability; Donors; Correlation; Principal component analysis